2015
DOI: 10.1080/1360080x.2015.1102822
|View full text |Cite
|
Sign up to set email alerts
|

Higher education as object for corporate and nation branding: between equality and flagships

Abstract: Branding has become an important issue within higher education. The use of core value statements and visions are expressions of this. To be a successful brand, organisations must also make sure they are different from others. However, in both the scholarly discourse and in political rhetoric, the Nordic model highlights equal access to education and opportunities for all. Values such as egalitarianism and diversity may be difficult to fit into a frame of reference where excellence is at the centre. Historicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…To cite by way of example the issue of university marketing, we see the relevance of our findings to experiences of both Nordic and Australian universities. There, recent research has shown how the confluence of different value systems has brought about conflict and compromise (Onsman, 2008;Sataøen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To cite by way of example the issue of university marketing, we see the relevance of our findings to experiences of both Nordic and Australian universities. There, recent research has shown how the confluence of different value systems has brought about conflict and compromise (Onsman, 2008;Sataøen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, promoting national higher education has recently become a very important part of nation branding for many countries. As claimed by Sataøen (2015), "different higher learning institutions become part of nation branding practices as they are used to promote the country for foreign students, employees and other stakeholders". Nation branding is widely referred to as a very complex and controversial concept, which sometimes has a negative aspect to it, being criticised for overemphasising the importance of commercialisation and marketing practices (Dinnie, 2015).…”
Section: Defining Nation Brandingmentioning
confidence: 99%
“…According to Dinnie, sectors such as tourism, investment or education could be the main focus of nation branding initiatives. Education is indeed considered by many authors as an important part of nation branding (Sataøen, 2015;Gade, 2014). With globalisation forcing the higher education sector to transform and become more competitive, reputation and branding in higher education start to play a vital role.…”
Section: Higher Education Branding As a Part Of Nation Brandingmentioning
confidence: 99%
“…However, it seems that it can be used on other sectors, in this case on the education and research, where the research is limited. Sataøen (2015) argues that countries which have adopted the Nordic model, which highlights equal access to education and opportunities for all, can be quite attractive since it creates the nation branding of a country which it is a country which fosters and supports free education. In addition to this, Sataøen (2015) refers to how different branding perspectives (corporate branding and nation branding) are matched and harmonized with respect to higher education in two Nordic countries, while universities are competing each other so to attract more funds, better personnel and more students from abroad.…”
Section: Nation Branding For Education and Researchmentioning
confidence: 99%
“…A recent paper (Sataøen, 2015) refers to the fact that branding has become an important issue within higher education but also among other educational institutes, such as research centers. The same rule applies for nations which seek not only to excel on education but also to attract a high volume of students, researchers and other academic staff, so as to improve the academic quality of their institutions but also to attract students who will pay fees and contribute on the local economy (Drori et al, 2013).…”
Section: Introductionmentioning
confidence: 99%